Corporality, emotion and oral discourse: An approach to the notion of pia among the Chanés of Northwest Argentina - Morando, Maria Agustina (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
The aim of this paper is to approach the representations about the verbal ways in which the Chanés of Northwest Argentina express emotions. The expression of the emotion is mainly associated with pɨa, an organ that acts as a locus par excellence of the expression of the states of mind of a person. Bearing this in mind, the focus here will be on the description the contexts and experiences of everyday Chané life in which emotions and its significance are culturally manifested. This work aims to contribute to the study of the social construction of the body and the conception of the person from the perspective of the verbal emotion.